An Improved EDAS Method Based on Bipolar Neutrosophic Set and Its Application in Group Decision-Making. (15th October 2021) - Irvanizam, Irvanizam; Syahrini, Intan; Zi, Nawar Nabila; Azzahra, Natasya; Iqbal, Muhd; Marzuki, Marzuki; Subianto, Muhammad
Abstract : The bipolar neutrosophic set is a suitable instrument to tackle the information with vagueness, complexity, and uncertainty. In this study, we improved the original EDAS (the evaluation based on distance from average solution) with bipolar neutrosophic numbers (BNNs) for a multiple-criteria group decision-making (MCGDM) problem. We calculated the average solution under all the criteria by two existing aggregation operators of BNNs. Then, we computed the positive distance and the negative distance from each alternative to the average ideal solution and determined the appraisal score of alternatives. Based on these scores, we obtained the ranking result. Finally, we demonstrated the practicability, stability, and capability of the improved EDAS method by analyzing the influence parameters and comparing results with an extended VIKOR method.